Examining Change in Family Conflict and Family Violence After Release From Prison - Stansfield, Richard (Criminal justice and behavior, 2020)
This study examines changes in family conflict and violence among a sample of adult men after release from prison. Using longitudinal panel data on 1,282 men in the Serious and Violent Offender Reentry Initiative, cross-lagged dynamic fixed-effects panel data models are used to examine factors that relate to family conflict and family violence perpetrated by men after release from prison. Increased contact with family members during incarceration, as well as postrelease family support, related to decreased family conflict, even after accounting for family conflict during incarceration. Contact was unrelated to postrelease family violence. Interestingly, family violence prior to incarceration did not predict within-person changes in violence postrelease. Postrelease substance use and criminal offending significantly related to postrelease family violence. With incarceration affecting so many people nationwide, understanding how the experiences of incarceration and reentry impacts family health and well-being should be an important consideration for correctional policy and programming.